Ceftriaxone as an Alternative Therapy for the Treatment of Methicillin-Susceptible Staphylococcus aureus Bacteremia after Initial Clearance of Bloodstream Infection - Barber, Katie E. (Case Rep Infect Dis, 2021)
INTRODUCTION: Staphylococcus spp. represent the leading cause of hospital-acquired infections and second-most frequent pathogen in bloodstream infections. Methicillin-susceptible S. aureus (MSSA) comprise approximately half of all S. aureus isolates. Standard-of-care therapies (SOCTs) display high treatment success but require frequent dosing, are problematic in penicillin allergic patients, and are nephrotoxic. Ceftriaxone may represent an alternative treatment option. METHODS: Adult patients hospitalized from January 2015 through June 2016 with positive MSSA blood cultures and treated with SOCT or ceftriaxone for ≥48 hours were included. Exclusion criteria were receipt of vancomycin or concomitant systemic antimicrobials with activity against MSSA, polymicrobial infections, and pregnant patients. Additional data collected included demographics, source/site of infection, and treatment. The primary endpoint was clinical cure (normalization of white blood cell count and temperature within 7 days and clearance of bloodstream within 7 days). Readmission within 60 days, length of stay, and discharge disposition were collected. RESULTS: A total of 43 patients were included: 23 receiving SOCT and 20 receiving ceftriaxone group. Sixteen patients received SOCT prior to ceftriaxone while 4 patients were initiated on ceftriaxone. Clinical cure was observed in 18/23 (78%) and 10/20 (50%), respectively (P=0.052). Clinical failure was driven by leukocytosis despite clearance of their bloodstream infection in 3/23 (13%) SOCT group compared to 8/20 (40%) in the ceftriaxone group (P=0.043). Six patients (SOCT: 2, ceftriaxone: 4; p=0.669) had infection-related readmissions, and 1 death per group was observed. CONCLUSION: Ceftriaxone poses a reasonable alternative to consider for MSSA bacteremia when cost and feasibility are concerns for outpatient parenteral therapy after initial clearance of bloodstream infections.